THE CONTRIBUTION OF RENTED HOUSES ENVIRONMENT IN MANAGING DISCIPLINE AMONG DAY PUBLIC SECONDARY SCHOOL STUDENTS IN TANZANIA: A CASE OF TABORA REGION - Augustino, Elizabeth; Bwagilo, Huruma O (Yayasan Education and Social Center, 2023)
This study investigated the contribution of rented houses environment in managing discipline among day public secondary school students in Tabora, Tanzania, specifically in Nzega District. A qualitative research approach was employed, coupled with a case study design. The study employed parents, landlords, and students as respondents.42 respondents were selected by using purposive sampling techniques. Moreover, data were collected through semi-structured interviews, focus group discussions, observation, and documentary review. Thematic analysis was used to analyze data. The study findings revealed that most rented houses did not support the management of students' discipline. Since only a few rented houses had borders, they needed fences, security guards, rules, and regulations to control students' fields. The study recommends that the Ministry of Education, Science, and Technology collaborate with the schools and community to build dormitories, reducing inconveniences as some parents are reluctant to send their children to schools far from their locations for safety reasons